Sejarah Untuk Mendapatkan Pengakuan Kedaulatan Republik Indonesia - Aprilzal, Teddy (Program Magister Pendidikan Sejarah FISH UNJ, 2023)
Abstract : This article was written to find out the recognition of the sovereignty of the Republic of Indonesia in the war that occurred as a result of the Dutch military aggression II which had the aim of destroying and annihilating the Republic of Indonesia from the results of the Proclamation of Indonesian Independence on August 17, 1945. The climax of this war was carried out through guerrilla warfare. to block the general attack on March 1, 1949. This recognition of the sovereignty of the Republic of Indonesia received support from various countries in Asia with the New Delhi conference organized by India and western countries, namely the United States. With the participation of the United States, Australia gave its support. The world reaction to the Dutch military aggression II was held by a session of the World Security Council (UN). Ir. Soekarno as a figure who has an important role and influence in Indonesia, the United Nations invited him and the Netherlands to carry out KMB negotiations which resulted in the Roem-Royem agreement which was held in Jakarta. Then several negotiations were held between Indonesia and the BFO which took place twice in the KMB. KMB is very historic and plays an important role in obtaining recognition of the sovereignty of the Republic of Indonesia which was declared by the Netherlands on December 27, 1949, that the Netherlands recognized the sovereignty of the Republic of Indonesia de facto and de jure.